Rane Willerslev: Soul Hunters. Hunting, Animism, and Personhood among the Siberian Yukaghirs - Matzen, Ida Sofie; Røjskjær, Lise; Svane, Lea; Torntoft, Louise (Tidsskriftet Antropologi, 2008)
Anmeldes af Ida Sofi e Matzen, Lise Røjskjær, Lea Svane & Louise Torntoft